INFLUENŢELE RECIPROCE DINTRE OM ŞI MEDIUL NATURAL (PANGEEA, 2025)
Mutual influences between humankind and the environment. To live better, people have gradually transformed the natural environment, considering that it may be used provided their support is not destroyed. Most often, talking about human impact on the environment, there are references to its pollution. Unfortunately, often, human aggression exceeds the field of pollution and is therefore more accurate to talk about different ways of deterioration and destruction of the environment.